A new expression for computing the bottomside thickness parameter and comparisons with the NeQuick and IRI-2012 models during declining phase of solar cycle 23 at equatorial latitude station, Chumphon, Thailand. Issue 2 (15th July 2017) - Jamjareegulgarn, Punyawi; Supnithi, Pornchai; Watthanasangmechai, Kornyanat; Yokoyama, Tatsuhiro; Tsugawa, Takuya; Ishii, Mamoru
Abstract: This paper proposes a new expression for computing the bottomside thickness parameter at equatorial latitude station, Chumphon (10.72°N, 99.37°E), Thailand. Its diurnal variations from 2004 to 2006 at this location are then studied. The proposed expression is derived based on two experimental data sources: FMCW ionosonde and dual-frequency GPS system, and some expressions of the NeQuick 2 model. Hence, after both the bottomside thickness parameter computed by the proposed equation, B2bot_Pro, and the bottomside shape parameter (namely, B1_Pro in this work) are computed, the bottomside electron density and the height where the bottomside electron density drops down to be 24% of the Nm F2 (namely, h0.24) can be computed and shown in this work using the analytical functions of the IRI model. Moreover, the diurnal variations of the B2bot_Pro are compared with those computed from the NeQuick model, B2bot_NeQ, and the predicted B0 of the IRI-2012 model with ABT-2009 and Bil-2000 options (namely, "B0_ABT" and "B0_Bil", respectively). The averaged, minimum, and maximum values of percentage deviations among these bottomside thickness parameters are also computed and shown in this work. Our results show that the diurnal variations of B2bot_Pro at Chumphon station have the following patterns: they start to increase during nighttime to the first peaks during pre-sunrise hours, and then decrease abruptly to their minimum values during sunrise hours. Afterward, they increase again to reach the second peaks around local noontime and fall gradually to their starting times during 20–04 LT. The diurnal variations of B2bot_Pro follow generally the same trends as those of the B2bot_NeQ and the B0_ABT, except pre-sunrise hours. The pre-sunrise peaks and sunrise collapses in both the B2bot_NeQ and the B0_ABT can be found occasionally. On the other hand, the diurnal variations in B2bot_Pro differ from those in B0_Bil due to the flattened variation in B0_Bil and the pre-sunrise peaks as well as sunrise collapses in B0_Bil disappear. The pre-sunrise peaks of the B2bot_Pro at the Chumphon station are higher than those of the B2bot_NeQ, the B0_ABT, and the observed B0 at other regions. Furthermore, the percentage deviations between the B2bot_Pro and the B0_ABT (PD_B2B0ABT) are mostly lower than 30% for all seasons of the studied years, opposite to the other percentage deviations studied in this work. The proposed B2bot_Pro parameters in this work follow a similar trend to the B2bot_NeQ and the B0_ABT, but it is not conclusive that the proposed values are equivalent to them.